SERUM ELECTROLYTE DERANGEMENTS IN PATIENTS WITH TRAUMATIC BRAIN INJURY - Rafiq, Mirza Faisal Ahmed; Ahmed, Noor; Khan, Adil Aziz (Journal of Ayub Medical College Abbottabad, 2013)
Background: Electrolyte derangements are common sequel of traumatic brain injury. Use of intravenous fluids, diuretics, syndrome of inappropriate ADH secretion and cerebral salt washing are some of the factors responsible for this. Proper in time detection followed by appropriate treatment not only improves neurological status but also decrease morbidity and mortality. This study was conducted to know serum derangements of different electrolytes in patients with traumatic brain injury. Methodology: This cross-sectional study was conducted in Pakistan Institute of Medical Sciences, Islamabad, Pakistan from Feb 2009 to Feb 2010. All adult patients with traumatic brain injury who presented to Neurosurgical department with severe head injury (GCS <8) and who need monitoring in high dependency unit, were included in this study. Initially twice daily serum electrolyte monitoring for one week then once daily for remaining period of hospital stay was carried out. All samples were sent to Pathology department of Pakistan Institute of Medical Sciences, Islamabad. Patients who need corrective measures for imbalance had repetition of sampling after giving appropriate therapy. Statistical analysis was performed on SPSS-16. Results: Total 215 patients presented with severe head injury that were managed in high dependency unit. Out of which 127 (59.1%) were male and 88 (40.9%) were females. Most of them were adults between 21-40 years of age (21.4%; 24.7%). Sodium was the main electrolyte that underwent change & out of which hyper-natremia was major abnormality that occurred in 140 (65.1%) of patients. This is followed by hypo-kalemia that occurred in 79 (36.7%) of patients. Serum calcium & magnesium levels show little derangements. Conclusion: Electrolyte imbalance following traumatic head injury is an important cause to look for in patient monitoring. Sodium is the chief electrolytes of concern. Serum potassium and calcium levels also under goes notable changes. Keywords: Traumatic brain injury, serum electrolyte derangements